Relevansi Parliamentary Threshold dan Sistem Kepartaian di Indonesia - Ansari, Ahmad Nur; Syamsu, Suhardiman; Ekawaty, Dian (LP2M IAIN Palopo, 2022)
This paper aims to show how the parliamentary threshold's implications for simplifying the party system in Indonesia. In addition, this paper also shows the role of political parties in democracies. This is important because political parties are pillars of democracy. The simplification of political parties is carried out as a consequence of the ideals of reform and constitutional amendments to strengthen the presidential system, where the presidential system is considered incompatible with the multi-party system, and the parliamentary threshold is believed to be one way to simplify political parties. The study compared the parliamentary threshold of 2.5% in the 2009 election with the parliamentary threshold of 3.5% in the 2014 election against the simplification of political parties. In the end, this paper shows that the increase in the parliamentary threshold from 2.5% in the 2009 election to 3.5% in the 2014 election has no implications for simplifying political parties at the time.Â